Multiobjective, trust‐aware, artificial hummingbird algorithm‐based secure clustering and routing with mobile sink for wireless sensor networks - Jemla Naik, Anil Kumar; Parameswarappa, Manjunatha; Ramachandra, Mohan Naik (ETRI journal, 2024)
Wireless sensor networks (WSNs) are composed of numerous nodes distributed in geographical regions. Security and energy efficiency are challenging tasks due to an open environment and a restricted battery source. The multiobjective trust‐aware artificial hummingbird algorithm (M‐TAAHA) is proposed to achieve secure and reliable transmission over a WSN with a mobile sink (MS). The M‐TAAHA selects secure cluster head (SCH) nodes based on trust, energy, interspace between sensors, interspace between SCH and MS, and the CH balancing factor. A secure route is found by M‐TAAHA with trust, energy, and interspace between SCH and MS. The M‐TAAHA avoids the malicious nodes to improve data delivery and avoid unwanted energy consumption. The M‐TAAHA is analyzed using energy consumption, alive nodes, life expectancy, delay, data packets received in MS, throughput, packet delivery ratio, and packet loss ratio. Existing techniques (LEACH‐TM, EATMR, FAL, Taylor‐spotted hyena optimization [Taylor‐SHO], TBEBR, and TEDG) are used for comparison with the M‐TAAHA. Findings show that the energy consumption of the proposed M‐TAAHA for 1000 rounds is 0.56 J (1.78 × smaller than that of the Taylor‐SHO).